A Comparative Analysis of Lipid Profile Parameters in Type 2 Diabetes Mellitus Patients Undergoing Statin Therapy in Tarhuna (مجلة العلوم الشاملة, 2025)
Type 2 Diabetes Mellitus (T2DM) is a prevalent metabolic disorder associated withdyslipidemia, which significantly increases the risk of cardiovascular diseases. Statin therapy iscommonly prescribed to manage lipid profiles in T2DM patients. However, the comparativeefficacy of different statins in this population remains underexplored, particularly in specificregional contexts such as Tarhuna City, Liby